Comparison of Endoscopic Tympanoplasty with Microscopic Tympanoplasty - Nousheen Qureshi , Muhammad Musharaf Baig , Misbah Parvez, Sundas Masood, Memoona Afzal, Nousheen Qureshi , Muhammad Musharaf Baig , Misbah Parvez, Sundas Masood, Memoona Afzal (Journal of Rawalpindi Medical College, 2020)
Background: Minimally invasive surgery has recently been developed along with endoscopic techniques. Endoscopic Ear Surgery is becoming popular with its anatomic and physiologic concepts. Tympanoplasty is one of the commonest operations performed for the middle ear. While using the endoscope we can place the graft accurately while avoiding unnecessary post or endaural incision and soft tissue dissections which are mandatory during tympanoplasty using a microscope. Our study was aimed to compare the outcomes of endoscopic and microscopic tympanoplasty in terms of graft uptake, hearing outcome and postoperative pain. Methods: This is a retrospective comparative study of 63 patients who underwent type 1 tympanoplasty at Holy Family Hospital ENT Department from March 2017 to March 2020. The subjects were classified into 2 groups; Endoscopic tympanoplasty (ET, n=30), Microscopic Tympanoplasty (MT, n=33). Type 1 Tympanoplasty, was the procedure done on patients of both the groups. Demographic data, perforation size of the tympanic membrane at preoperative state, pure tone audiometric results preoperatively and 3 months postoperatively, operation time, sequential postoperative pain scale (NRS-11), and graft success rate were evaluated. Results : The perforation size of the tympanic membrane in the Endoscopic group and the microscopic group was nearly the same (p=.877). Pre and post-operative air-bone gaps including air and bone conduction thresholds were not significantly different between the two groups. The graft success rate in the endoscopic and Microscopic group was 93.3% and 63.3% respectively; the values were significantly different(p=0.0046). Immediate and 6 hours postoperative pain was similar in both the groups, however pain on ist postoperative day was significantly lower in the endoscopic group. Conclusion: We can do minimal invasive tympanoplasty with the help of endoscopes with better graft success rate, less preoperative time, and less postoperative pain.